AU‐ARROW (Australia): World‐wide FINGERS network: The first global network of multidomain dementia prevention trials. (7th December 2020) - Martins, Ralph N; Anstey, Kaarin J; Baker, Laura D.; Barin, Edward; Dias, Cintia B; Brown, Belinda M; Burnham, Samantha C; Chatterjee, Pratishtha; Chen, Juliana; Clarnette, Roger; Deang, Kristine; England, Tim; et al.
Abstract: Background: The highly encouraging findings from the Finnish Geriatric Intervention Study (known as FINGER) led to the global initiative for dementia risk reduction known as world‐wide FINGERS (WW FINGERS). As part of the collaboration, our Australian AU‐ARROW trial will follow the general protocol of the FINGER trial, and will also be aligned with the U.S. arm of the study, US‐POINTER, though will have minor cultural and dietary modifications to determine the validity of the intervention in an Australian setting. Method: AU‐ARROW is a randomised, single‐blind 2‐year clinical trial that will recruit 600 participants aged 60‐79 satisfying specific inclusion/exclusion criteria, including normal cognition and one or more cardiovascular risk factors that place them at greater risk of cognitive decline. Participants will be distributed across two sites (a) Macquarie University Health Clinics, Sydney, NSW and (b) Sarich Neuroscience Research Institute, Edith Cowan University, Perth, WA, and will be randomised equally into either the innovative multi‐modal intervention group or the study control group, who will receive general lifestyle advice and annual health check‐ups, without treatment. Multi‐modal intervention consists of aerobic exercise, resistance training and stretching; dietary advice with monitoring to encourage adherence to the MIND diet; cognitive training sessions via the Brain HQ computerised online training system; and medical monitoring and regular health education sessions. Heart rate trackers, diet and exercise log books, and the monitoring of Brain HQ sessions will all help with adherence. Primary outcome measure is improvement in global cognitive score, measured using neurocognitive tests identical to those in the US‐POINTER protocol. Additional neurocognitive tests, physical function improvements, detailed diet monitoring and sleep monitoring will provide added data. The unique extra value of AU‐ARROW trial consists of the testing for Alzheimer's disease (AD) blood biomarkers in all participants; as well as the AD Aβ amyloid‐specific ligand‐PET imaging, brain MRI and retinal biomarker tests that half of the participants will undergo. These tests will provide comprehensive data which have the ultimate purpose of increasing knowledge of the preclinical stages of AD, and help not only to develop preclinical AD diagnostic tests but also efficacy of AU‐ARROW's intervention.